Communication Relations Strategy North Sumatra Regional Police in Building Police Image in North Sumatra, Indonesia - Rudangta Ginting; Iskandar Zulkarnain; Dewi Kurniawati (Journal of Social Interactions and Humanities, 2023)
This aims at analyzing the communication strategy of North Sumatera Provincial Police Public Relation to build the image of police in North Sumatera. This qualitative research employs a phenomenological approach. The findings of the research indicate that the communication strategy of the Public Relation Division of North Sumatera Provincial Police focuses on the use of media, such as online media, social media, or printed media. The willingness of the North Sumatera Provincial Police Force to provide training and coaching for personnel, technological support, and collaboration with other institutions and society have been identified as effective factors in the Provincial Police Force's communication strategy to build the image of police. The public, on the other hand, believes that the communication strategy implemented by the Public Relations of North Sumatera Provincial Police to improve police image is ineffective.